STUDY OF HAIR ZINC LEVELS AND HEMOGLOBIN LEVELS OF STUNTING AND NON STUNTING TODDLERS IN TILANGO PUSKESMAS, GORONTALO REGENCY - Zihan S. Zakaria; Margaretha Solang; Dewi Wahyuni K. Baderan (Journal Health & Science : Gorontalo Journal Health and Science Community, 2022)
Abstract                 Stunting is a major nutritional problem that will have an impact on social and economic life in society. Stunting can affect children under five in the long term so that it interferes with their health, education and productivity in the future. Improving nutritional status is one of the eight goals to be achieved in the Millennium Development Goals (MDGs). The novelty of this research is the level of examining differences in hair zinc and hemoglobin levels of stunting and non-stunted toddlers.The purpose of this study was to determine differences in zinc levels, Hb levels and how they affect children who suffer from stunting and non-stunting. The research method uses observational analytic methods using a case control design. The population in this study was divided into two, namely the population of children under five years of age 0-59 months suffering from stunting and non-stunting. Test the difference between Hb and Zinc using an independent t test. Binary logistic regression analysis was used to see the effect of Hb and Zinc on the incidence of stunting. The results of the study found that there was an effect of Hb and Zinc on stunted and non-stunted children, namely Hb had an effect of 0.637 with a P-value of the Wald test (sig.) of 0.602 or 0.05 and Zinc had an effect of -0.059 with a P-value of the Wald test. (sig.) of 0.116 or 0.05. Conklusion the better the zinc level, the lower the incidence of stunting in children, but it is not significant to the incidence of stunting.Abstrak Stunting merupakan masalah gizi utama yang akan berdampak pada kehidupan sosial dan ekonomi dalam masyarakat. Stunting dapat berpengaruh pada anak balita pada jangka panjang sehingga mengganggu kesehatan, pendidikan serta produktifitasnya di kemudian hari. Perbaikan status gizi menjadi salah satu dari delapan tujuan yang akan dicapai dalam Millenium Development Goals (MDGs). Kebaruan penelitian ini adalah meneliti perbedaan kadar Zinc Rambut dan kadar Hemoglobin Balita stunting dan non stunting. Tujuan penelitian ini yakni mengetahui perbedaan kadar zinc, kadar Hb dan bagaimana pengaruh pada anak yang menderita stunting dan non stunting. Metode penelitian menggunakan metode analitik observsional dengan menggunakan desain case conrol. Populasi pada penelitian ini dibagi menjadi dua yakni populasi anak balita 0-59 bulan yang menderita stunting dan non stunting. Uji perbedaan Hb dan Zinc menggunakan uji t independent. Analisis regresi logistic biner digunakan untuk meilhat pengaruh Hb dan Zinc terhadap kejadian stunting. Hasil penelitian menemukan  terdapat pengaruh Hb dan Zinc terhadap anak stunting dan non stunting yakni Hb berpengaruh sebesar 0,637 dengan nilai P-value uji Wald (sig.) sebesar 0,602 atau 0,05 dan Zinc berpengaruh sebesar -0,059 dengan nilai P-value uji Wald (sig.) sebesar 0,116 atau 0,05. Kesimpulan Semakin bagus kadar zinc maka akan semakin mengurangi  terjadinya stunting pada anak namun tidak signifikan terhadap kejadian stunting.    Kata kunci: Stunting, Hb, zinc